Pendidikan Karakter Keluarga Islami Abad 21 Berdasarkan Q.S. Al-Isra’ Ayat 23–24 - Ariya Supena (La-Tahzan: Jurnal Pendidikan Islam, 2026)
Amid the challenges of modern development and moral degradation in the contemporary era, character education within the Islamic family has become an essential foundation for shaping a generation with noble morals and virtuous character. This study aims to examine character education within Muslim families in the 21st century based on the teachings of Surah Al-Isra’ verses 23–24. This research uses a qualitative method with a library study approach and thematic tafsir analysis of relevant Qur’anic verses. The results show that Surah Al-Isra’ verses 23–24 contain essential character education values, namely the instillation of tauhid (the oneness of Allah) and birrul walidain (filial piety). These values include prohibitions against associating partners with Allah, encouragement to do good to both parents, prohibitions against speaking harshly or scolding them, encouragement to speak gently, to be humble toward parents, and to pray for them. The implementation of Qur’anic values in family education in the modern era helps shape children with noble character, excellent personality, and constant devotion to their parents. These findings confirm that the principles of Islamic character education, rooted in the Qur’an, remain relevant in the 21st century and can serve as a strategic foundation for shaping a generation of insan kamil (well-rounded individuals) both physically and spiritually.